Artificial Intelligence in Healthcare - Shaik, Ramjan (Indian Journal of Pharmacy Practice)
Since a created thing first takes form within the mind of its creator, it is in some sense a part or an extension of its creator and thus definitionally lesser. Our creations rarely surprise us, and when they do, it’s either because of a bug in the design or because we are unable or unwilling to simulate its emergent behavior to a high enough degree of fidelity.